Potential role of endogeic earthworm in mitigating blood disease in banana plant - Teng, Suk Kuan (2016)
Banana is an important fruit crop in many tropical countries including Malaysia. Besides the threat of Fusarium wilt and Moko disease, the occurrence of blood disease in Malaysia is another challenge to the cultivation. Therefore, there is an urgent need to search for effective treatment against the disease. Endogeic earthworms are known as soil fauna that improve soil properties and promote plant health, through their feeding, burrowing and casting activities. The present study aimed to evaluate the effect of Pontoscolex corethrurus (a common endogeic earthworm in the tropics) on blood disease in banana. Field sampling was conducted in a banana plantation infected with bacterial wilt disease. Identification of the causal pathogen was then carried out with morphological and molecular approaches. The pathogen obtained was confirmed to be blood disease bacterium (BDB). Secretions (cast and mucus) and soil inoculated with P. corethrurus were obtained to be tested on BDB in vitro. The results showed that earthworm mucus promoted the growth of Pseudomonas sp. that inhibited BDB. The interaction between P. corethrurus, BDB and banana was further evaluated through a glasshouse experiment. In the study, infected banana plantlets with earthworm inoculation showed less disease severity compared to un-inoculated ones, suggesting the role of endogeic earthworms in remediating blood disease. The finding was supported by nuclear magnetic resonance (NMR) and multivariate data analysis (MVDA) that revealed the presence of different groups of metabolites in the roots of the plantlets when inoculated with earthworms and BDB. The study suggested the potential role of endogeic earthworms (P. corethrurus) in enhancing soil microbial population and serve as possible bioremediation agent in plant disease management. Field trial and further investigations on the mechanisms that govern the changes are therefore essential to gain better understanding of this earthworm-BDB-host interaction.